Plastic Optical Fiber with Sol-gel Film for pH Detection. (2017) - Razo-Medina, D.; Alvarado-Méndez, E.; Trejo-Durán, M.
Abstract: In this work, the development of plastic optical fiber with sol-gel for pH detection is shown. Sol-gel technique is used by immobilizing phenolphthalein, litmus on surface of an optical plastic fiber. The light of a LED (632 nm wavelength) is transmitted through the optrode. The variations of intensity of the light output are detected by a photoresistor, this intensity changes according to pH of the sample. The percent transmittance versus unit of pH is presented in characteristic curve.